Analysis of the Incidence and Risk Factors in the Development of Acute Kidney Injury after Off Pump Coronary Artery Bypass Grafting (Academia Journal of Medicine, 2021)
Background: Acute kidney injury (AKI) is a serious complication after coronary artery bypass grafting and is associated with a high mortality. The aim of this study was to evaluate the incidence and the risk factors involved in the development of AKI after off pump coronary artery bypass grafting (OPCAB). Subjects and Methods: A retrospective analysis of 1378 adult patients who underwent OPCAB in Sapthagiri Institute of Medical Sciences and Research Centre during a one-and-a-half-year period was done. AKI was defined as an increase in creatinine more than 0.3 mg/dl or a decrease in urine output less than 0.5 ml.kg.hr for 6 hrs. The data relevant to the risk factors were collected and analysed using chi square test. Results: The overall incidence of AKI was 18.2%. The independent risk factors that were associated with AKI were increasing age, pre-operative chronic kidney disease, diabetes mellitus, left ventricular dysfunction, low mean arterial blood pressure and the need for intra-aortic balloon pump. Conclusion: AKI was common after OPCAB. Pre-existing renal dysfunction, diabetes mellitus, left ventricular dysfunction, advanced age, low mean arterial blood pressure during the intra operative period and the need for intra-aortic balloon pump were identified as the risk factors for the development of AKI after OPCAB.
Keywords: Acute kidney injury; Coronary artery disease; Graft